Location of a biliary leak after liver resection determines success of endoscopic treatment - Schaible, Anja; Schemmer, Peter; Hackert, Thilo; Rupp, Christian; Schulze-Schleithoff, Anna; Gotthardt, Daniel; Büchler, Markus W.; Sauer, Peter (Surgical endoscopy and other interventional techniques, 2017)
Background: Bile leaks after hepatic resection are serious complications associated with substantial morbidity and mortality. The aim of this prospective observational study was to determine the therapeutic success of endoscopic treatment of biliary leakage after liver resection. Patients and methods: Grade B biliary leaks were considered for endoscopic treatment in patients after liver resection between 1/09 and 4/12. Endoscopic treatment (sphincterotomy only, plastic stent distal to leak or bridging) was defined as successful when the patient remained without symptoms after drain removal and without extravasation follow-up ERC 8 weeks later. Results: Overall rate of biliary leak was 7.4 % (61/826). 35 patients with a grade B bile leak were considered for endoscopic treatment. 22 (63 %) had bile leaks that were peripherally located, and 13 (37 %) had bile leaks at central location. In 3 patients, sphincterotomy only was performed; in 19 patients, a stent distal to the leak and in 13 patients, a bridging stent was inserted. The overall success rate was 74 % (26/35 patients). Endoscopic treatment failed in 26 % (9/35), and mortality rate was 11 % (4/35). In all patients with leaks located at the right or left hepatic duct, treatment with the bridging stent was successful. Conclusion: Endoscopic therapy for biliary leakage after liver resection is safe and effective and should be considered as a first-line therapy in patients who are suitable for an interventional, non-surgical approach. Patients with a centrally located leak who are treated with a bridging stent are more likely to benefit from endoscopic intervention.
Published online: 17 August 2016
Gesehen am 04.10.2016